The aesthetic experience of general beauty and ugly-cute memes: the role of emotion - Li, Juan; An, Yi; Xia, Tiansheng (Frontiers in Psychology, 2024)
Generally, beauty has been regarded as an outward expression of elegance and harmony, providing visual pleasure and evoking a sense of aesthetic enjoyment. However, in recent years, a phenomenon called “ugly-cute” has emerged, challenging the conventional standards of beauty by embracing a form of “ugliness” to enhance its appeal. The reasons and mechanisms behind this phenomenon remain largely unexplored so far. This study aims to investigate the role of emotions, such as pleasure, humor, and surprise, in the relationship between ugly-cute characteristics and attractiveness. The findings reveal that general beauty directly generates attractiveness by eliciting pleasurable emotions, whereas ugly-cute memes achieve attractiveness by inducing pleasurable emotions through the mediation of humor. Furthermore, while both “ugly” and “ugly-cute” memes evoke a sense of surprise, that elicited by ugly-cute memes is accompanied by a humorous response, thereby enhancing their attractiveness, whereas the “ugly” memes fail to evoke humor and lack attractiveness. Finally, we discuss the potential implications and practical value of the current research.